Serratia marcescens Endocarditis with Perivalvular Abscess Presenting as Atrioventricular Block - Aaron Richardson; Andres Martinez; Shreya Ghetiya; Emil Missov; Robert Percy; Srinivasan Sattiraju (Case Reports in Infectious Diseases)
Serratia marcescens is an aerobic, Gram-negative bacillus first identified in 1819 (Yeung et al. 2018). S. marcescens infective endocarditis is extremely rare accounting for only 0.14% of all cases (Phadke and Jacob 2016, Hadano et al. 2012, Nikolakopoulos et al. 2019). We present the case of a 33-year-old male with a past medical history of Hodgkin lymphoma, nonischemic cardiomyopathy ejection fraction of 25–30%, severe aortic stenosis, hepatitis C, and active intravenous (IV) drug abuse who was admitted following a motor vehicle accident. Approximately 10 days into his admission, he developed a 39.5 degree Celsius fever, which prompted collection of blood cultures. These cultures were positive (2 out of 2) for S. marcescens for which he was treated with intravenous cefepime. Soon after this diagnosis, patient developed a complete AV block. Given the instability of the patient, he required emergent placement of a temporary pacing wire. Transesophageal echocardiogram was ordered and revealed an aortic root abscess. Given the comorbidities and active IV drug use, conservative management was pursued. Although rare, trends suggest that this pathogen may be on the rise. Further research is needed to better understand how to effectively manage this pathogen.